The late turn-out of the Slovak star-up factories: locational and institutional factors - Oto Hudec; Marek Lavcak (European Regional Science Association (ERSA), 2015)
In recent years, start-ups and creative industries economy have recorded an extraordinary expansion. The geography of start-up and creative industries is often coincident with the factors of agglomeration economies and networking assets together with talent inherence and managerial culture, which are supposed to be similar for both appearances.In Slovakia, the government has recognized its interest in the agenda of start-ups and creative industries only recently (2013), but the private and non-profit sector has predicted this trend three years before, when in Bratislava, the capital of Slovakia, the first major co-working spaces with an integrated approach to education and support of innovative business emerged. A support in the second largest city Ko?ice started institutionally only in 2014, in the premises of its Technical University. The start-up ecosystems in both cities have different focus, size, evolutionary qualities and culture, as their birth and fast growth was influenced by existing different regional innovation system and attracted rather different groups of young people. The comparison of both start-up and art scenes in its early phase, only marginally touched by the public incentives, gives a possibility to study the start-up ecosystems in their uncontaminated form, based mostly on the interviews of the start-up owners, gurus, venture capitalists, enthusiasts and observers.
Keywords: O; R; 330; start-up; creative industries; regional diversity; development; entrepreneurship